Mortalidade materna por Covid-19 no estado do Pará: um estudo descritivo do período de 2020 a 2021 - OLIVEIRA, Suel do Nascimento de (2023)
Introduction: the correlation between maternal mortality and the covid 19 pandemic has become the target of several studies in Brazil and in the world, which showed an increased risk of death in obstetric patients when compared to non-pregnant women. The objective of this research is to describe how the increased risk, promoted by the infection, affected pregnant and postpartum women in the state of Pará in the period between 2020 and 2021. Methods: this is a descriptive, retrospective and cross -sectional study. Secondary databases were used: Brazilian obstetric observatory covid-19, in addition to the Information System on Mortality and Birth Rates. The information was grouped and organized in the form of graphs and tables using the Excel 2016 program. Results: a total of 302 cases of severe acute respiratory syndrome (SARS) by covid-19 were observed, of which 41 died between 2020 and 2021. There was a predominance of deaths in women: black, with low education, mean age of 30 years and between the third trimester of pregnancy and the postpartum period. Most of the fatal cases occurred in the metropolitan region of Belém and at least 34% of the deaths occurred without access to an intensive care unit bed, while 36% did not receive invasive ventilatory support.. Moreover, an increase in Maternal Mortality Rate (MMR) was observed in the last two years, with an inversion in the proportion of direct and indirect deaths. Discussion: such findings can be attributed to an increased risk of serious illness associated with infection by covid-19 in pregnant women, in addition to a chronically fragile and deficient health system, which in the pandemic context, affected from prenatal consultations in basic health units, to assistance for SARS cases in the country's maternity hospitals. In addition, the contribution of the increase in deaths from covid-19 to the increase in MMR in the last two years should be highlighted. Conclusions: the increase in MMR due to indirect causes, associated with the current epidemiological scenario, express the participation of deaths from covid-19 in the increase in this index. It is also noteworthy that the profile of fatal cases is predominantly of black women, with a lower level of education and between the third trimester of pregnancy and the postpartum period.